MOBILE CONTROL LAND MINE DETECTING ROBOT USING ARDUINO - Srinivasulu, K.; ganapathy, Kirupa (International Journal of Psychosocial Rehabilitation, 2020)
the Anti criminals in the society are danger to the human life. To safeguard the life of the human the current technology is involved for their security. The main aim of this paper is to develop the robot to detect the bomb in the land mine of the earth surface. This system is more helpful in the defense system. The ATMEGA controller is used to perform the regular operation. The two ends points are created the receiving point and the transmitting point. When the proximity sensor is detects the bomb in the land the information is send to the receiver region. The data transmission is takes place through the radio frequency system. The RF transmitter transmits the data from the controller and the data is received by the RF receiver. The frequency range between the two medium is about 20MHz. The data interference is avoided in the particular frequency range and the noise can be totally neglected. This method is more useful to the solider in the defense area.